Ultramicroporous carbon with extremely narrow pore distribution and very high nitrogen doping for efficient methane mixture gases upgrading - Yao, Ke Xin; Chen, Yanli; Lu, Yue; Zhao, Yunfeng; Ding, Yi (Carbon (New York), 2017)
It is notably challenging to fabricate heavily heteroatom-doped porous carbonaceous materials with narrow ultramicropore size distributions for highly effective mixed-gas separation. In this study, new carbon-based materials with narrow ultramicropore size (<7 Å) distributions (>95%) and high N doping contents (>10 at%) are fabricated through the pyrolysis of a perchloro-substituted porous covalent triazine-based framework (ClCTF). In particular, the sample prepared at 650 °C (ClCTF-1-650) possesses the highest ultramicropores content (98%) and large N content (12 at%) and demonstrates a very high CH4 and CO2 capacity, as well as a low N2 uptake under ambient conditions. The extraordinarily high CH4/N2 and CO2/N2 selectivities correlate with both the ideal adsorption solution theory (IAST) method and performed dynamic separation experiments (breakthrough experiments). The results reported in this study far exceed the CH4/N2 and CO2/N2 selectivities of previously reported carbon-based adsorbents including various nitrogen-doped ones. These results are believed to be associated with the unusually high N content, as well as the suitably narrow ultramicropore size distribution. This report introduces a new pathway to design porous absorbents with precisely controlled ultramicropores for gas separation. [Display omitted]